Analysis of Teacher Personality Competence in Improving Role Modeling in Students at SMA Negeri 1 Parlilitan - Risma Mawarni Barutu (Jurnal Pendidikan LLDIKTI Wilayah 1 (JUDIK), 2025)
This study aims to analyze the personality competency of educators in improving role models in the school environment. Personality competency is one of the important components in teacher professionalism, including integrity, responsibility, moral role models, and emotional stability. The research method used is descriptive qualitative with data collection techniques through observation, in-depth interviews, and documentation studies of teachers in two secondary schools at SMA Negeri 1 Parlilitan. The results of the study indicate that teacher personality competency has a significant effect on exemplary behavior displayed in schools, especially in aspects of discipline, honesty, and concern for students. This study recommends strengthening personality development in teacher training programs as a strategic step to improve role models in schools.